Climatic influences on the growth rates of Mn crusts during the Late Quaternary - Eisenhauer, Anton; Gögen, K.; Pernicka, Ernst; Mangini, Augusto (Earth and planetary science letters, 1992)
The concentration of230Th in Mn crust VA13-2 (146°W, 9°25′S, 4830 m) from the Pacific Ocean was measured with high depth resolution (0.02 mm) to a depth of 1.4 mm corresponding to an age of ∼226 ka B.P. The mean growth rate estimated from these results is6.2 ± 0.4 mm/Ma. However, the exponential curve obtained shows two drastic events in the230Th concentration record with durations of41 ± 4 ka and37 ± 6 ka which are interpreted as growth standstills. The decay-corrected230Th concentration is inversely correlated with those of Mn, Fe and Co indicating that the230Th flux into the crust has been constant throughout time and that the observed fluctuations in230Th are due to dilution by the main components. By applying a constant230Th flux model, high-resolution growth rates were derived from every sample investigated. A detailed comparison of the growth pattern with the SPECMAP time table reveals that the VA13-2 growth rates tend to be higher during interglacial than during glacial periods. In particular, the observed growth standstills are associated with glacial stages 6 and 8. Further investigation of Mn crust 72 DK 9 taken from shallower water (170°35′W, 20°13′N, 1550 m) tend to confirm that there is a link between the growth rates of hydrogenetic crusts and the climate of the Late Quaternary.
Elektronische Reproduktion der Druck-Ausgabe 23. Oktober 2002
Gesehen am 30.03.2023